MANAGEMENT OF GUILLAIN BARRE SYNDROME THROUGH AYURVEDA-A CASE STUDY - E Pady, *Amritha; Dr, Muralidhara; Dr, Shridhar; A, Byresh (International Journal of Ayurveda and Pharma Research, 2017)
Guillain-BarrÃ© syndrome (GBS) is an acute, rapidly evolving are ï¬‚exic motor paralysis with or without sensory disturbance. It occurs year around at arate of between 1 and 4 cases per 100,000 annually. Age is an important factor determining outcome, and prognosis. In children is said to be favourable as compared to adults. Direct correlation of GBS with Ayurvedic terminology is difficult. The presentation and Doshadooshyasamoorchana is considered first and then one should proceed with the treatment. Here a case of 7 year old female child presented with sudden onset of loss of power in lower limb, unable to get up, walk and stand with a past history of fever brought to OPD of SKAMC&HRC Bangalore. She was provisionally diagnosed as a case of acute inflammatory demyelinating polyneuropathy (AIDP-type of GBS). As per Ayurvedic classics, this condition we have taken as Sarvangavata (Vata affecting the whole body) which precedes Jwara (H/O fever before onset of symptoms). Hence, the line of treatment we have adopted Jwara Chikitsa and Vatavyadhichikitsa which included Aamapachana as well as Brihmanachikitsa along with Shamanoushadhis. The outcome was very remarkable with the patient able to walk on her own.